2018
DOI: 10.1007/s11356-018-1795-7
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing environmental monitoring and assessment of the long-term impacts of the February 2014 radiological release from the waste isolation pilot plant

Abstract: Three years ago, the Waste Isolation Pilot Plant (WIPP) experienced its first minor accident involving a radiological release. Late in the evening on February 14, 2014, a waste container in the repository underwent a chemical reaction that caused the container to overheat and breach, releasing its contents into the underground. Following a lengthy recovery process, the facility recently resumed waste disposal operations. The accident released significant levels of radioactivity into the disposal room and adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…WIPP was closed for three years after the incidents, and analyses have indicated that there were several internal DOE problems leading to the accidents including mismanagement at Los Alamos National Laboratory (for the canister that leaked), physical structure problems at WIPP, and a breakdown of nuclear culture (Klaus, 2019). Fortunately, both immediate and longer term monitoring has determined that the level of exposure for workers or the public was below the limit set by EPA (Thakur & Runyon, 2018). Dr. Regalbuto was instrumental in addressing these problems, leading to WIPP's eventually opening.…”
Section: See the Facility As The Workers See Itmentioning
confidence: 99%
“…WIPP was closed for three years after the incidents, and analyses have indicated that there were several internal DOE problems leading to the accidents including mismanagement at Los Alamos National Laboratory (for the canister that leaked), physical structure problems at WIPP, and a breakdown of nuclear culture (Klaus, 2019). Fortunately, both immediate and longer term monitoring has determined that the level of exposure for workers or the public was below the limit set by EPA (Thakur & Runyon, 2018). Dr. Regalbuto was instrumental in addressing these problems, leading to WIPP's eventually opening.…”
Section: See the Facility As The Workers See Itmentioning
confidence: 99%